KOMUNIKASI ANTARBUDAYA MINANGKABAU DAN MANDAILING DALAM PROSES AKULTURASI PERNIKAHAN DI NAGARI UJUNG GADING PASAMAN BARAT - Reka Mindaling; Darul Ilmi (ADISAM PUBLISHER, 2023)
This study aims to describe the background of the occurrence of cultural mixing in the Nagari Ujung Gading area, West Pasaman Barat, the Minangkabau and Mandailing ethnic groups have special cultural motifs that focus on their respective cultures. Each of the migrant communities undergoes exchanges because they have to adapt to a new area, be it lifestyle, ways of getting along, and other social ties. This background is then raised by researchers into the formulation of the problem regarding what are the wedding activities originating from Minangkabau, then what are the wedding activities originating from Mandailing, how is the process of intercultural communication occurring in the process of culturation in Mandailing and Minangkabau ethnic marriages, and what are the obstacles in the process of acculturation of different ethnic marriages. The research process was carried out using qualitative methods with a descriptive approach. It aims to observe and describe the condition of a traditional wedding ceremony of Sumando and Manjujur which is located in the border area. Data collection in this study was carried out by interviews and observations to observe the various activities carried out by the Datuok, Penghulu, Niniak mamak, the bride and groom, the parents of the bride and the local community in traditional wedding ceremonies. The results of this study are two different cultures in Nagari Ujung Gading, namely Mandailing and Minangkabau, resulting in acculturation. In accordance with this acculturation theory, significant changes often occur in a tradition, even though changes occur in practice, this does not change the original purpose of the tradition